Development of a GFCF diet pocketbook for social work vocational high school students - ABDILAH, GALANG RAKA; Maslikah, Siti Imroatul (Talenta Publisher Universitas Sumatera Utara, 2025)
Students of the Social Work Vocational Program at SMK Bhakti Luhur face challenges in understanding and applying Gluten-Free Casein-Free (GFCF) diet interventions for children with Autism Spectrum Disorder (ASD). This lack of understanding affects their readiness as future social workers to provide dietary-based services for children with special needs. To address this issue, a community service activity was conducted through training and the development of a GFCF diet pocketbook tailored to the characteristics of vocational students. The pocketbook contains educational material on the principles of the GFCF diet, lists of recommended and prohibited foods, cooking tips, and practical guidelines for daily application. The activity adopted a project-based learning approach, starting with material delivery followed by hands-on practice in preparing GFCF menus. Evaluation was conducted using pre-test and post-test assessments on 125 students, showing a 43.6% increase in understanding. The Wilcoxon test indicated a significant improvement (Z = -7.560, p < 0.05), and the average N-Gain score was 0.301, classified as moderate. The pocketbook served not only as a training tool but also as a self-learning resource. This initiative is expected to enhance students' capacity to support community-based nutritional interventions for children with ASD.